Quadratus Lumborum Block for Analgesia After Cesarean Section: A Randomized Controlled Trial. Issue 4 (December 2020) - Irwin, R.; Stanescu, S.; Buzaianu, C.; Rademan, M.; Roddy, J.; Gormey, C.; Tan, T.
Abstract : ( Anaesthesia . 2020;75:89–95) Effective pain management after cesarean delivery is crucial both for maternal satisfaction with their delivery experience and their ability to devote their care and attention to their newborns. Neuraxial opioids have been a mainstay of postcesarean pain management, but there are significant drawbacks with these medications, including the potential for misuse. Another analgesic option for postcesarean analgesia is the quadratus lumborum block (QLB). The literature has indicated that QLB is safe and easy to perform after cesarean delivery and has shown superiority over transversus abdominis plane block. Yet, adding QLB to a standard multimodal analgesic regimen that includes intrathecal morphine has not yet been evaluated. The aim of this study was to assess the efficacy of QLB when added to a standard protocol that includes intrathecal morphine for the management of postcesarean pain after cesarean delivery.